Fast Distance-based Outlier Detection using GPUs - Mussel, Fernando; Teixeira, Carlos; Meira Jr., Wagner (Anais do Concurso de Trabalhos de Iniciação Científica da SBC (CTIC-SBC); 2015: Anais do XXXIV Concurso de Trabalhos de Iniciação Científica da SBC, 2015)
Outlier detection is an important area of data mining with many practical applications, such as credit card and insurance fraud detection, network intrusion detection, etc. Distance-based detection methods, such as ORCA and DIODE, have stood out due to their parametric-free nature and good scalability on large and high dimensional datasets. In this paper we propose, a new parallel algorithm based on ORCA, which is designed to run efficiently on GPUs (Graphical Process Units). Then we discuss the main challenges pertaining its implementation and how we addressed them, in order to take full advantage of the GPU’s parallel hardware. In our experimental analysis, we show that our algorithm not only is able to efficiently prune unnecessary distance computations, but can also achieve up to 162X speedup compared to state-of-the-art anomaly detection algorithms.